The CD163 + tissue-infiltrating macrophages regulate ferroptosis in thyroid-associated ophthalmopathy orbital fibroblasts via the TGF-β/Smad2/3 signaling pathway - Xuemei Li; Siyi Wang; Hanwen Cao; Simin Xu; Chao Xiong; Jinhai Yu; Yunxiu Chen; Zhangjun Ren; Min Li; Ying Hu; Puying Gan; Qihua Xu; et al. (Journal of Translational Medicine)
Abstract Background Thyroid-associated ophthalmopathy (TAO) is a thyroid function-related, organ-specific autoimmune disease that primarily leads to specific reactive changes and tissue remodeling in the periocular region. The exact pathogenesis of TAO remains unclear. Methods High-throughput gene expression datasets related to TAO were comprehensively retrieved from the Gene Expression Omnibus (GEO) database, selecting GSE174139 and GSE158464 for analysis. Differentially expressed genes (DEGs) between TAO patients and healthy controls were identified, and ferroptosis-related genes (FRGs) were obtained from the FerrDb database. The intersection of DEGs and FRGs yielded ferroptosis-related genes associated with TAO.The transcriptional expression of FRGs was validated using real-time quantitative polymerase chain reaction (RT-qPCR) on orbital adipose tissue samples from TAO patients and healthy controls. Single-cell sequencing of six human tissue samples further analyzed changes in cellular subpopulations within the TAO microenvironment.Additionally, a co-culture model of CD163 + macrophages and TAO orbital fibroblasts, along with an in vitro TGF-β1-induced orbital fibroblast (OF) model, was constructed to validate the role of the TGF-β1/SMAD2/3 axis in ferroptosis regulation. Finally, potential clinical drugs targeting CD163 + macrophages with high ferroptosis activity in TAO were predicted using the Random Walk with Restart (RWR) algorithm combined with the DGIdb database. Results We first utilized TAO-related datasets from the GEO database, combined with the FerrDb ferroptosis database, to identify changes in iron metabolism genes during TAO progression through differential expression analysis, screening 7 key ferroptosis-related proteins. In vitro validation revealed that all but AOPQ and LGMN, which were upregulated, exhibited downregulated expression.Single-cell sequencing of orbital connective tissue from 4 TAO patients and 2 healthy controls identified 16,364 cells spanning 18 cell types. Analysis of the 7 key ferroptosis-related proteins revealed that fibroblasts and macrophages displayed elevated ferroptosis signaling during TAO progression. Subcluster analysis of macrophages identified 4 distinct subpopulations, with the C2 subpopulation—characterized by high expression of CD163 and CCL18—exhibiting prominent ferroptosis activation signals.Further validation using clinical tissue samples, a co-culture model of CD163 + macrophages and TAO orbital fibroblasts, and an in vitro TGF-β1-induced orbital fibroblast (OF) model confirmed aberrant activation of the TGF-β1/SMAD2/3 pathway as a key regulator of ferroptosis. Hub gene analysis of C2 subpopulation marker genes, combined with the DGIdb database, predicted potential clinical drugs targeting the C2 macrophages. Conclusion This study, integrating single-cell RNA-Seq and bulk transcriptome analysis, revealed the involvement of CD163 + tissue-infiltrating macrophages in regulating ferroptosis of orbital fibroblasts during TAO progression and identified therapeutic candidates targeting macrophage ferroptosis signaling in TAO. Furthermore, in vitro experiments demonstrated that activation of the TGF-β1/SMAD2/3 axis promotes ferroptosis in TAO orbital fibroblasts, highlighting a novel pathway for potential therapeutic intervention.